Digital Subtraction Angiographic Study of Circle of Willis in Indian Population in a Tertiary Super-Specialty Hospital (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Circle of Willis is an anastomotic polygon at the base of the brain which forms an important collateral network to maintain adequate cerebral perfusion. Changes in the normal morphology of the circle may causes the appearance and severity of symptoms of cerebrovascular disorders, such as aneurysms, infarctions and other vascular anomalies.Objectives: The aim of the present study was to analyses the anatomical variations of the circle of Willis by observing the variations in the cerebral arterial circle and was to clarify the clinical importance of these variations in certain forms of cerebrovascular diseases.Methodology: This cross-sectional study was conducted in the department of Neurointervention of Max Super-speciality Hospital, New Delhi, India and Neo multispeciality Hospital, Noida, Uttar Pradesh (UP), India during July 2016 to December 2016 for a period of six (6) months. Patients who were admitted in the Neurointervention department for digital subtraction angiography (DSA) were included in this study. The circle of Willis was then analyzed with the special reference to the complete or incomplete circle, any asymmetry in the configuration and variations in the size, and number of the component vessels, circle with multiple anomalies and absence, fenestration, duplication or triplication of any of the vessels.Results: Morphology and variations of the circle of Willis were studied in 74 patients undergone digital subtraction angiography (DSA). The normal pattern of circle of Willis was observed in 40(54.06%) cases and the remaining 34(45.94%) cases had one or more variations; however, 24(70.58%) cases had variations in the anterior circulation and 10(29.42%) cases had variations in the posterior circulation. 17(50%) cases had variations on the right side compared to 13(38.24%) variations on the left side. 4(11.76%) cases had variations in the anterior communicating artery. Incomplete circle of Willis were found 12(35.28%) cases. Multiple variations were observed in 11 cases (32.35%) in this study. In 4 cases anterior communicating artery aneurysms were observed.Conclusion: Variation of circle of Willis is common in this study of Indian population.Journal of National Institute of Neurosciences Bangladesh, 2017;3(2): 99-105